Controle autonômico cardíaco sob condições de repouso, exercício e pós-exercício em indivíduos com lesão medular: um estudo observacional do tipo seccional - (:unkn) unknown (Centro Universitário Augusto Motta, 2020)
Individuals with spinal cord injury (SCI), especially in high injuries, show changes in cardiac autonomic control resulting, for example, in lower maximum heart rate. The best knowledge of the physiological aspects of individuals with SCI is fundamental for the most adequate structuring of the training routine with physical exercises in order to provide a better general health status. The general objective of the study was to evaluate cardiac autonomic control at rest, during a test of maximum progressive effort and immediately after effort in individuals with SCI, comparing them with individuals without SCI. Methods: A sectional study was carried out with 09 individuals with quadriplegia, 08 with paraplegia and 10 without SCI (control group). The cardiac autonomic control was investigated through the analysis of heart rate variability (HRV) indexes obtained through the electrocardiogram (ECG) and the cardiofrequencymeter. For the analysis at rest, the participants sat for 10 minutes in the morning. Then, a maximum cardiopulmonary exercise test (CPET) was performed on a cycle ergometer for upper limbs, with increasing intensity, followed by a passive recovery period of 10 minutes, in the sitting position. For comparison between groups, the Kruskal-Wallis test was performed (when a significant difference was found, the Mann Whitney U test was used). The validity of HRV indices (ECG versus CPET and ECG versus cardiofrequencymeter) was verified by calculating the intraclass correlation coefficient and using Altman and Bland's graphical approach. The relationship between HRV rest indexes and rMSSD during recovery was analyzed by Spearman's test. We used the Friedman test to analyze intra-group parasympathetic reactivation in the moments after CPET. The level of statistical significance was 5% (SPSS 20.0). Results: The agreement between heart rate variability threshold (LiVFC) and the first ventilatory threshold (LV1) showed an ICC of 0.908 for VO2 in quadriplegics, whereas the agreement between ECG and cardiofrequency meter showed ICC values between 0.850 and 0.952 for VO2 in groups with SCI. The relationship between HRV indices and parasympathetic reactivation was significantly positive for HF indices (0.77 to 0.94, p <0.05). and rMSSD (0.68 to 0.96, p <0.05). Conclusion: Agreement was found between LiVFC and LV1, just as the cardiofrequency meter was found to be valid to identify LiVFC. Parasympathetic reactivation seems to be influenced by the HRV indices at rest.
Keywords: Sistema nervoso autônomo; Exercício físico; Tetraplegia; Paraplegia; Reabilitação; Fisioterapia e Terapia Ocupacional